The All-Russian Competition for the best projects for comfortable urban environment in small towns and historic settlements - Kosareva, Tatyana (project baikal, 2018)
The article reviews the procedure and the results of the All-Russian competition for the best projects for comfortable urban environment in small towns and historic settlements organized in May 2018. It points out the interest among citizens towards the proposed projects and their focus on revealing the cultural identity of small towns and historic settlements. The article describes the procedure of public defence of the winning projects and information support of the competition.